Technical-economic evaluation of a 94.5 MW wind power plant at different elevation heights. A case study in Peru's countryside - Portocarrero Mendoza, Priscila Scarlet (2024)
Artículo sustentado el 29 de mayo 2024 para la obtención del título profesional de Ingeniera de la Energía.